Influenza infection in neutropenic adults. Issue 2 (1st February 2017) - Durani, Urshila; Dioverti Prono, Maria V.; Tosh, Pritish K.; Patnaik, Mrinal; Barreto, Jason N.; Tande, Aaron J.
Abstract: While lymphopenia is a well-defined risk factor for severe influenza, the effect of neutropenia is unknown. This was a retrospective single centre study of adult patients with documented neutropenia and influenza between 2005 and 2013. Forty patients were included with a median follow-up of 2 years (IQR 0.8–4.0). Median ANC at influenza diagnosis was 0.3 × 10 9 /L (IQR 0.1–0.4 × 10 9 /L). Outcomes included hospitalization ( N  = 28, 70%), pneumonia ( N  = 9, 23%), ICU admission ( N  = 9, 23%) and mechanical ventilation ( N  = 7, 18%). Three deaths (7.5%) were attributed to influenza, all of whom had lower respiratory tract infection (LRTI). Patients with LRTI ( N  = 18, 45%) also had a higher 30-day mortality (37 versus 0%) and 90-day mortality (42 versus 0%) than those with upper respiratory tract infection. In summary, neutropenic patients have high rates of influenza complications. Our study highlights the need for early diagnosis and aggressive management of influenza in this population.